Association between triglyceride glucose index, coronary artery calcification and multivessel coronary disease in Chinese patients with acute coronary syndrome - Wang, Jiayu; Huang, Xianwei; Fu, Caihua; Sheng, Qiping; Liu, Ping (Cardiovascular diabetology, 2022)
Background Multivessel coronary disease (MVCD) is the common type of coronary artery disease in acute coronary syndrome (ACS). Coronary artery calcification (CAC) has been confirmed the strong predictor of major adverse cardiovascular events (MACEs). Several studies have validated that triglyceride glucose (TyG) index can reflect the degree of coronary calcification or predict MACEs. However, no evidence to date has elucidated and compared the predictive intensity of TyG index or/and coronary artery calcification score (CACS) on multi-vascular disease and MACEs in ACS patients. Methods A total of 935 patients, diagnosed with ACS and experienced coronary computed tomography angiography (CCTA) from August 2015 to March 2022 in the Second Hospital of Shandong University, were selected for retrospective analysis. The subjects were divided into TyG index quartile 1–4 groups (Q1-Q4 groups), non-multivessel coronary disease (non-MVCD) and multivessel coronary disease (MVCD) groups, respectively. The general data, past medical or medication history, laboratory indicators, cardiac color Doppler ultrasound, CACS, and TyG indexes were respectively compared among these groups. The ROC curve preliminarily calculated and analyzed the diagnostic value of TyG index, CACS, and the combination of the two indicators for MVCD. Univariate and multivariate logistic regression analysis discriminated the independent hazard factors for forecasting MVCD. Results Compared with the lower TyG index and non-MVCD groups, the higher TyG index and MVCD groups had higher values of age, smoking history, waist circumference, systolic blood pressure, low-density lipoprotein cholesterol(LDL-C), fasting blood glucose and glycosylated hemoglobin, and CACS, but lower values of high-density lipoprotein cholesterol(HDL-C) (all P < 0.01). Coronary artery calcification is more common in the left anterior descending artery. Compared with non-MVCD, each unit increase in TyG index was associated with a 1.213-fold increased risk of MVCD. Logistic regression analysis adjusted for potential confounders indicated that TyG index is an independent risk factor for MVCD. With the increase of TyG index, the incidence of MACEs, apart from all-cause death, cardiac death, unexpected re-hospitalization of heart failure, recurrent ACS or unplanned revascularization, and non-fatal stroke in coronary artery increased (P log-rank < 0.001). Conclusion TyG index could completely substitute for CACS as a reliable, practical, and independent indicator for predicting the severity and prognosis of MVCD in patients with ACS.